Invisible victims of development: workers health and safety in Asia - Pandita, Sanjiv; George, Oumana; Choi, Sally; Wulandari, Sri (Hong Kong, 2012)
"Report on Invisible Victims of Development – Workers Health and Safety in Asia: is an effort by the Asia Monitor Resource Centre (AMRC) to highlight the severity of the problem on the ground in Asia with a detailed report from 6 Asian countries – China, India, Cambodia, Philippines, Thailand and Indonesia. The absence of figures also highlights the invisibility of impacted workers and their families and most of the time even denial about their existence by governments in the region. Yet they exist on the ground- impacted due to hazardous conditions at work and denied justice in terms of compensation, rehabilitation and dignity forming the most marginalised and exploited section of society."